Nanotechnology for Age-Related Macular Degeneration - Bo Yang; Ge Li; Jiaxin Liu; Xiangyu Li; Shixin Zhang; Fengying Sun; Wenhua Liu (MDPI AG, 2021)
Age-related macular degeneration (AMD) is a degenerative eye disease that is the leading cause of irreversible vision loss in people 50 years and older. Today, the most common treatment for AMD involves repeated intravitreal injections of anti-vascular endothelial growth factor (VEGF) drugs. However, the existing expensive therapies not only cannot cure this disease, they also produce a variety of side effects. For example, the number of injections increases the cumulative risk of endophthalmitis and other complications. Today, a single intravitreal injection of gene therapy products can greatly reduce the burden of treatment and improve visual effects. In addition, the latest innovations in nanotherapy provide the best drug delivery alternative for the treatment of AMD. In this review, we discuss the development of nano-drug delivery systems and gene therapy strategies for AMD in recent years. In addition, we discuss some novel targeting strategies and the potential application of these delivery methods in the treatment of AMD. Finally, we also propose that the combination of CRISPR/Cas9 technology with a new non-viral delivery system may be promising as a therapeutic strategy for the treatment of AMD.